Efficacy of the Treatments Used in Multiple Sclerosis: From Meta-analysis to Number Needed to Treat - García-Ruiz, Antonio J.; Izquierdo-Ayuso, Guillermo; Navarro-Mascarell, Guillermo; Montesinos-Gálvez, Ana Carmen; Martos-Crespo, Francisco; Jódar-Sánchez, Francisco; Correa, manuel; García-Agua-Soler, Nuria (Lippincott Williams & Wilkins, 2017)
The aim of this study was to analyze the efficacy of drugs used in relapsing-remitting multiple sclerosis, first- and second-line drugs, using the number needed to treat (NNT) as a measure of efficacy. Methods: Data from randomized clinical trials were analyzed for 3 categories of clinical efficacy outcomes: relapse, change in Expanded Disability Status Scale, and number of new lesions in magnetic resonance imaging. Meta-analysis results are expressed as odds ratios. Results: The global odds ratio was 0.41 (95% confidence interval [CI], 0.34-0.49). For analyzed clinical outcomes, the odds ratio was less for second-line drugs (odds ratio, 2.0). For all studied clinical conditions, in the control group, 47 of 100 patients do not get benefits, compared with 25 (95% CI, 18-32 patients) of 100 for the active treatment group. The NNT was 5 patients (95% CI, 4-7 patients). For the proportion of patients free of relapses, in the control group, 56 of 100 patients had a relapse at 2 years, compared with 37 of 100 patients in the treatment group, with an NNT of 6 patients (95% CI, 5-8 patients). Conclusions: Active treatments produced statistically significant improvements compared with placebo.
Keywords: Esclerosis múltiple; Eficacia; Número necesario a tratar; Meta-análisis